UPAYA MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS VIII MELALUI MODEL PEMBELAJARAN GAME BASED LEARNING (GBL) BERBANTUAN GAMES ULAR TANGGA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SD-SMP SATU ATAP 4 GUNUNG SARI - Aulia Sawilakmah; Lalu Sumardi; Humamurrizqi Humamurrizqi (Jurnal Manajemen Pendidikan, 2026)
This study aimed to determine whether the implementation of the Game Based Learning (GBL) model assisted by game media could improve the learning activeness of eighth-grade students in the Pancasila Education subject at SD-SMP Satu Atap 4 Gunung Sari. This research employed a Classroom Action Research (CAR) design conducted in three cycles, consisting of the stages of planning, action, observation, and reflection. The research subjects were 25 eighth-grade students of SD-SMP Satu Atap 4 Gunung Sari. Data were collected through observation, questionnaires, and documentation. The results showed that the implementation of the Game Based Learning (GBL) model assisted by the snake and ladder game successfully improved students’ learning activeness progressively in each cycle. In Cycle I, the percentage of students’ learning activeness reached 56%, categorized as moderately active. In Cycle II, it increased to 76%, categorized as active, following improvements in the learning process. Furthermore, in Cycle III, the percentage increased to 92%, categorized as very active. The improvement was reflected in students’ willingness to ask and answer questions, express opinions, collaborate in groups, and actively participate in educational game activities during the learning process.